Passively q-switched 11 channels stable brillouin erbium-doped fiber laser with graphene as the saturable absorber - Ahmad, Harith B.; Zulkifli, Mohd Zamani; Muhammad, Farah Diana; Jemangin, M. H; Dimyati, Kaharudin; Pal, Bishnu Pada; Harun, Sulaiman Wadi (IEEE, 2012)
A passively Q-switch Brillouin-Erbium Doped Fiber Laser (BEDFL) with 11 stable lasing wavelengths at peak power of -15 dBm between 1550.1 nm to 1551.0 nm, 1.67 µs pulse width and repetition rate of 152.40 kHz is demonstrated. The proposed BEDLF uses a 7.7 km Dispersion Compensating Fiber (DCF), assisted by an Erbium Doped Fiber Amplifier (EDFA) to generate the multi-wavelength output by Stimulated Brillouin Scattering. A graphene layer embedded in the laser cavity acts as a saturable absorber, allowing for Q-switched pulses.